Bromatological analysis of beef and pork meat sold in the province of Tungurahua - Delgado Ramos, Andrea Verónica; Pérez Aldás, Lander Vinicio (SATHIRI, 2024)
Beef an pork is a product of high demand in the Ecuadorian market, its nutritional content makes it important in the daily diet, it has: protein, fat, vitamins and minerals. However, despite the benefits it provides, some medical recommendations limit its consumption due to its high fat content, which makes it a precursor of important cardiovascular diseases. The objective of this research was to analyze the bromatological composition of beef and pork marketed in the Province of Tungurahua. The beef had a moisture content of 74.96 ± 5.97%; 4.03 ± 0.97% ash; 0.99 aw; 6.24 ± 0.45 pH; and 10.70 ± 6.44% total fat. Similarly, the analysis of pork meat showed a moisture content of 69.50 ± 7.50%; 3.89 ± 1.17% ash; 0.99 in aw; 6.36 ± 0.26 in pH; and 33.15 ± 5.29 for pork meat. Therefore, the meats analyzed had acceptable water composition, are DFD meats, with high ash and lipid content.